2012
DOI: 10.7773/cm.v38i3.2012
|View full text |Cite
|
Sign up to set email alerts
|

Capture-recapture abundance estimate of Guiana dolphins in southeastern Brazil

Abstract: ABSTRACT. The objective of this study was to estimate the abundance of Sotalia guianensis in Sepetiba Bay, southeastern Brazil, based on photographic identification of animals. Estimates of population size were obtained using capture-recapture models for a closed population. Photo-identification data were analyzed using a model-fitting approach in the computer programs CAPTURE and MARK, and the Schnabel and Schumacher-Eschmeyer estimators were used to calculate the abundance of individuals with natural marks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…To manage elasmobranch species sustainably and design efficient conservation programmes, accurate information on the population dynamics of these marine predators is necessary. The first step to estimate the population size, and thus understand the population dynamics of a particular species, is to identify the different individuals of a population (Bradshaw et al, 2007;Freitas-Nery, 2012). Marine biologists use a great variety of methods for marking and identification purposes, from simple and passive methods, such as external tags, to active methods like electronic tags (Hammerschlag et al, 2011).…”
mentioning
confidence: 99%
“…To manage elasmobranch species sustainably and design efficient conservation programmes, accurate information on the population dynamics of these marine predators is necessary. The first step to estimate the population size, and thus understand the population dynamics of a particular species, is to identify the different individuals of a population (Bradshaw et al, 2007;Freitas-Nery, 2012). Marine biologists use a great variety of methods for marking and identification purposes, from simple and passive methods, such as external tags, to active methods like electronic tags (Hammerschlag et al, 2011).…”
mentioning
confidence: 99%
“…We performed boat-based surveys between August 2005 and December 2011 in Sepetiba Bay, southeastern Brazil, where one of the largest populations of Guiana dolphins, estimated to be thousands of individuals (Flach et al, 2008a;Nery & Simão, 2012), is found. Sighted groups of dolphins were slowly approached and followed, while an attempt was made to take pictures of all group members, with no preference, using a digital SLR camera Canon 40D equipped with a 100 to 400 mm lens (Flach, 2006).…”
mentioning
confidence: 99%
“…While the changes observed in the Guiana dolphins of Sepetiba Bay are associated with human‐induced rapid environmental change, it is important to note that possible demographic changes caused by the morbillivirus outbreak, as well as the differences between the time series in sampling effort, may have had a major influence on the results of the present study. Abundance estimates from 2002 to 2006, when Sepetiba Bay was considered to be a closed population, indicate that the bay was inhabited by 1000–1269 individuals (Flach, Flach & Chiarello, 2008; Nery & Simão, 2012). In a subsequent estimate, in 2012, also considering it a closed population, Flach (2015) reported a population of between 588 and 1004 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The population also had a large proportion of groups with calves, which used the bay primarily to breed and feed (e.g. Erber & Simão, 2004; Flach, Flach & Chiarello, 2008; Nery & Simão, 2012; Oliveira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%